Knowledge, Faith, Morality, and the Future of Humanity - Muhammed Haron (International Institute of Islamic Thought, 2010)
The International Symposium on Bediuzzaman Said Nursi, held in Istanbul from 3-5 October 2010 under the auspices of Istanbul Ilim ve Kültür Vakfi (www.sempozyum2010.com and www.barlaplatformu.com), coincided with the fiftieth anniversary of this great Muslim social reformer’s death. Its theme, “Knowledge, Faith, Morality, and the Future of Humanity,” attracted academics, scholars, and writers from around the world who sought to explore and examine The Risale-i Nur’s contributions to human peace, prosperity, and happiness. The 106 peer-reviewed papers presented were divided into three separate volumes according to language: Turkish (13 papers), Arabic (50 papers), and English (43 papers and the keynote address).